2019
DOI: 10.1002/pd.5615
|View full text |Cite
|
Sign up to set email alerts
|

Maceration determines diagnostic yield of fetal and neonatal whole body post‐mortem ultrasound

Abstract: Objectives:To determine factors in nondiagnostic fetal and neonatal post-mortem ultrasound (PMUS) examinations. Methods:All fetal and neonatal PMUS examinations were included over a 5-year study period (2014)(2015)(2016)(2017)(2018)(2019). Nondiagnostic image quality by body parts (brain, spine, thorax, cardiac, and abdomen) was recorded and correlated with patient variables.Descriptive statistics and logistic regression analyses were performed to identify significant factors for nondiagnostic studies. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 29 publications
0
15
0
1
Order By: Relevance
“…Whilst we focussed on image quality in this study, a recent diagnostic accuracy study showed that maceration rendered up to 50% of imaging non-diagnostic, in particular for the brain [ 20 ] and heart [ 9 , 30 ], although analysis at autopsy is equally extremely challenging. Further optimisation of micro-CT may help provide greater diagnostic yield in future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst we focussed on image quality in this study, a recent diagnostic accuracy study showed that maceration rendered up to 50% of imaging non-diagnostic, in particular for the brain [ 20 ] and heart [ 9 , 30 ], although analysis at autopsy is equally extremely challenging. Further optimisation of micro-CT may help provide greater diagnostic yield in future.…”
Section: Discussionmentioning
confidence: 99%
“…Minimally-invasive imaging techniques which are more acceptable to parents [ 3 5 ] have been developed to determine the causes of miscarriage and stillbirth, and to assist in the planning of future pregnancies [ 6 10 ]. Most current clinically available scanning methods do not provide sufficient image resolution of smaller fetuses [ 9 , 11 ], necessitating trialling higher resolution techniques [ 10 , 12 – 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…the 'post-mortem interval') has not been reported as a major factor in diagnostic postmortem imaging quality, the degree of maceration does (relating to time between intra-uterine foetal demise and delivery, so-called intra-uterine retention time). This has been reported to be the most significant factor in acquiring a diagnostic quality post-mortem ultrasound study [16,17] due to the degree of tissue breakdown and laxity of skull sutures. It would therefore be helpful to preferentially acquire an MRI where maceration is known to be extensive (usually when the intra-uterine retention time is estimated > 24 h).…”
Section: What Imaging Modalities Are Best Suited For Perinatal Post-mortem Imaging?mentioning
confidence: 99%
“…The highest sensitivity rates were found for brain imaging (84%) and lowest for cardiothoracic abnormalities (51%). It is important to note that extensive maceration reduces the diagnostic quality of the imaging, particularly for brain imaging [16,17]. Where there is maceration or a need to confirm and characterise an underlying cardiac anomaly, post-mortem MRI may be the more appropriate imaging modality.…”
Section: Ultrasoundmentioning
confidence: 99%
“…По данным S. Shelmerdine с соавт. [33] именно мацерация является основным фактором, снижающим эффективность УЗИ погибших плодов и новорожденных, особенно для выявления патологии головного мозга и сердца.…”
Section: посмертная мрт оценка давности внутриутробной гибели плодаunclassified